2022
DOI: 10.1186/s12884-022-04503-7
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the silence about obstetric violence: Body mapping women’s narratives of respect, disrespect and abuse during childbirth in Bihar, India

Abstract: Background Evidence on obstetric violence is reported globally. In India, research shows that almost every woman goes through some level of disrespect and abuse during childbirth, more so in states such as Bihar where over 70% of women give birth in hospitals. Objective 1) To understand how women experience and attach meaning to respect, disrespect and abuse during childbirth; and 2) document women’s expectations of respectful care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
0
22
0
3
Order By: Relevance
“…This explanation parallels other literature in the area ([ 19 , 29 , 30 ] . The same experience was also there in India where the sister (nurse) gave a laboring woman two tight slaps across her face [ 31 ] .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This explanation parallels other literature in the area ([ 19 , 29 , 30 ] . The same experience was also there in India where the sister (nurse) gave a laboring woman two tight slaps across her face [ 31 ] .…”
Section: Discussionmentioning
confidence: 90%
“…Nigerian study also explained that women suffered of being insult by obstetric care providers [ 7 , 29 , 30 ]. The study in India also showed the birth experience of women as the nurses committed verbal abuse by shouting at the laboring women [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that the persons who are disadvantaged by location, race, class, gender and other power differentials are denied voices, they are ill-treated by the system (Goetz and Jenkins, 2002; Mukhopadhyay and Meer, 2004). For example, rude behavior of health staff toward women availing reproductive health services was reported in many Indian states (Murthy, 1999; Mayra et al. , 2022; Sudhinaraset et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that the persons who are disadvantaged by location, race, class, gender and other power differentials are denied voices, they are ill-treated by the system (Goetz and Jenkins, 2002;Mukhopadhyay and Meer, 2004). For example, rude behavior of health staff toward women availing reproductive health services was reported in many Indian states (Murthy, 1999;Mayra et al, 2022;Sudhinaraset et al, 2016) and abuse of nurses was reported by the women availing obstetric services in several African countries (Jewkes et al, 1998;Shimoda et al, 2020;Oluoch-Aridi et al, 2018;Mapumulo et al, 2021). The lack of accurate information, which is fundamental for the utilization of health services, is an important challenge leading to poor access as seen in past research (Jacobs et al, 2012;Thakur, 2016;Kusuma et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research with women about their sensitive embodied experiences poses significant challenges when discussing their lived experiences of healthcare. In some country’s contexts and cultures, such as India, it is uncomfortable and/or taboo for women to discuss reproductive and sexual health and needs, contributing to the embarrassment stemming from a strong culture of silence and shame around it (Bhatt, 2018; Mayra et al, 2022; Pande et al, 2016; Paul et al, 2017; Santhya et al, 2010; Yari et al, 2015). These challenges are compounded by the gender and power differentials between them and people around them, in the home and obstetric environment (Sprague, 2016).…”
Section: Introductionmentioning
confidence: 99%